Performance of Healthy Braced Participants During Aerobic and Anaerobic Capacity Tasks - Rishiraj, Neetu (The National Athletic Trainers' Association, Inc., 2011)
CONTEXT: Knee braces were introduced in sports approximately 30 years ago. However, the effects of a functional knee brace (FKB) on aerobic and anaerobic performance after fatigue are unknown. OBJECTIVE: To investigate whether FKB use in noninjured participants hindered performance during aerobic (Léger beep test) and anaerobic (repeated high-intensity shuttle test [RHIST]) tasks. DESIGN: Crossover study. SETTING: Laboratory. PATIENTS OR OTHER PARTICIPANTS: Twenty-seven healthy male provincial and national basketball and field hockey athletes (age = 19.4 ± 3.0 years, range, 17–26 years; height = 182.6 ± 6.8 cm, range, 168–196 cm; mass = 80.0 ± 9.1 kg, range, 66–108 kg). INTERVENTIONS : Each participant was provided a custom-fitted FKB and performed 5 nonbraced (NBR) testing sessions over 3 days, followed by 5 braced (BR) testing sessions over 3 days, for a total of 17.5 hours of testing per condition. During each testing session, participants performed 1 trial of the Léger beep test and 1 trial of the RHIST in each condition. MAIN OUTCOME MEASURE(S): Predicted maximal oxygen consumption (V˙o(2)max) and time performance measures were recorded for each NBR and BR trial. RESULTS: Initial performance levels were lower for BR than NBR for both the Léger beep test (BR = 44.3 mL/kg/min, NBR = 47.3 mL/kg/min; F(1,26) = 8.726; P = .007) and the RHIST (BR = 16.5 seconds, NBR = 16.2 seconds; F(1,26) = 13.98, P = .001). However, with continued FKB use, the aerobic performance measure remained higher for only the first 2 BR testing sessions (NBR = 46.9 mL/kg/min, BR = 42.4 mL/kg/min; F(3.0,79.8) = 4.95, P = .003). For the anaerobic test, no performance difference was noted between the testing conditions (NBR = 16.2 seconds, BR = 16.4 seconds; P = .7), whereas fatigue levels were lower during BR testing sessions (NBR = 33%, BR = 31%). After 14.0 hours of FKB use, performance levels were almost equal between the testing conditions (NBR = 47.6 mL/kg/min, BR = 46.1 mL/kg/min). CONCLUSIONS: We found an initial decrement in performance when the FKB was used during an aerobic or anaerobic task. However, after 14.0 hours of FKB use, accommodation to the FKB was possible.